PENGARUH MOBELIK BERBASIS KEUNGGULAN LOKAL JENANG KUDUS TERHADAP PEMAHAMAN KONSEP PADA SISWA KELAS IV SEKOLAH DASAR 03 KARANGMALANG - Della Septianing Putri; Sekar Dwi Ardianti; Lintang Kironoratri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Active learning with a scientific approach can make students' understanding of concepts less than optimal. To find out students' understanding of concepts, it is necessary to have encouragement from the teacher. The problem of this research is how to influence the application of environmental learning modules based on the local advantages of Jenang Kudus on natural science learning materials on changes in the state of matter. This study aims to determine the effect of environmental learning modules based on local advantages of Jenang Kudus on students' understanding of the concept of material changes in state of matter at SD 03 Karangmalang. Mobelik, namely teaching materials that are motivated by environmental conditions so that students are more familiar with and love the potential that exists around the environment where students live. This research will be conducted in class IV of Elementary School 3 Karangmalang with 28 students as research subjects. This type of research is a quantitative study using the pre-experimental design method, type one group pretest-posttest. Data collection techniques were carried out using interviews, observation, tests, and documentation. The data analysis used was descriptive and inferential statistical data analysis. This t-test uses pretest and posttest values where the results are sig (2-tailed) <0.05, that is 0.00 <0.05, then H0 is rejected and H1 is accepted where there is a significant influence from the application of the Jenang Kudus Local Excellence-based Mobelik module on science learning material changes in substance form class IV. Based on the results of the N-Gain test, it proved that there was an increase when the Jenang Kudus local excellence-based mobile module was implemented. there was an increase after being given treatment using the mobile module based on the local advantages of Jenang Kudus.